The Issues Of Facemask Among Hajj Pilgrims: A Critical Review - Shahrul Anuwar, Mohamed Yusof; Imran, Abdullah; Irfan, Mohamad (2014)
Over 2 millions people congregate in Mecca every year to perform Hajj. Pilgrims are exposed to air-borne transmitted disease during this overcrowding period. Several measures have been practiced to reduce the spread of disease particularly the respiratory tract related infection. One of the preventive measures is by using face mask. Nevertheless, the use of face mask among pilgrims is shown to be only partially effective. This is attributed to the knowledge on the air borne transmitted disease, attitude towards wearing, technique of application, and to some extent the design of the face mask itself.